1983
DOI: 10.1002/j.1460-2075.1983.tb01645.x
|View full text |Cite
|
Sign up to set email alerts
|

The p36 substrate of tyrosine-specific protein kinases co-localizes with non-erythrocyte alpha-spectrin antigen, p230, in surface lamina of cultured fibroblasts.

Abstract: Biochemical and immunofluorescence studies have demonstrated that p36, a major substrate for the tyrosinespecific protein kinases induced by several sarcoma viruses and epidermal growth factor, is associated with plasma membranes and detergent-resistant cytoskeletal structures of cultured cells. We have used here polyclonal antisera and monoclonal antibodies in indirect immunofluorescence microscopy to study the subcellular location of p36 and the p230, which is a subplasmalemmal polypeptide showing immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 52 publications
4
31
0
Order By: Relevance
“…The sequence obtained for p10 confirmed and extended by eight residues that previously derived for the p36-plO complex. The p1O sequence (positions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] was then used in a computer search of known amino acid sequences (Protein Identification Resource Databank, Na-…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequence obtained for p10 confirmed and extended by eight residues that previously derived for the p36-plO complex. The p1O sequence (positions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] was then used in a computer search of known amino acid sequences (Protein Identification Resource Databank, Na-…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation assays were performed with 250 pug of p36-plO complex per mi/10 mM Tris HCl/0.05 M KC1/5 mM MgCl2/1 mM CaCl/0.5 mM dithiothreitol, pH 6.8, containing [10][11][12][13][14][15][16][17][18][19][20] ACi of [y-32P]ATP (1 Ci = 37 GBq) (Amersham). Under these conditions, incorporation was <1% (mol/mol) but it could be increased with additional pp6(V-src.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, biochemical and immunocytochemical studies support the idea that it mainly locates at the inner surface of the plasma membrane (5)(6)(7)(8)(9). In cultured cells, it remains on the cytoskeletal meshwork even after cells are permeabilized with detergent (10,11). Like erythrocyte spectrin, it also binds to globular (G) and filamentous (F) forms of actin, resulting in an increased viscosity of actin filaments in vitro (12,13).…”
mentioning
confidence: 94%
“…In some cases, however, stimulation of fibroblasts with epidermal or platelet-derived growth factor (18-20) is not accompanied by increased 34-kD protein phosphorylation . In addition, phosphorylation of this protein does not appear to be required for transformation of some cells by tyrosine kinase encoding retroviruses; several cell lines transformed by Abelson murine leukemia virus do not contain detectable amounts of the 34-kD protein (21).Recently, the 34-kD tyrosine kinase substrate has been localized at the inner surface of the plasma membrane by immunofluorescence staining (22-24) and subcellular fractionation studies (22,(24)(25)(26)(27) and was observed by immunofluorescence staining to have a distribution in chick or human embryo fibroblasts similar to that of the cytoskeletal associated protein a-spectrin (22,28). However, the role of the 34-kD protein in cellular transformation by retroviruses as well 473 on May 7, 2018 jcb.rupress.org Downloaded from…”
mentioning
confidence: 99%